PENGARUH PENGGUNAAN CELEBRITY ENDORSER TERHADAP PEMBENTUKAN BRAND IMAGE (Studi Pada Smartphone Oppo - Muthya Rahmi Darmansyah (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
This research aimed to analyze the effect of visibility, credibility, attraction and power of celebrity endorser toward brand image of smartphone Oppo in Medan City. The population in this study are Medan city society that have seen smartphone Oppo commercial starring Indonesian young multitalented celebrities. The sample was taken by purposive sampling using Cochran formula, with a total sample of 100 people. The data collection technique is by using questionnaires. Data analysis technique is done by multiple regression analysis and hypothesis testing t-test. The results of this study indicate that elements of visibility, credibility, attraction, power celebrity endorser significant and has positive impact on brand image of smartphone Oppo in Medan City. Keywords: Visibility, Credibility, Attraction, Power, and Brand Image